Implementasi P5 (Proyek Penguatan Profil Pelajar Pancasila) Di Mi Ikhlasiyah Palembang - Arina Hidayati; Ibrahim Ibrahim; Dewi Asri; Imelda Imelda; Indah Pajar Wati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research is about the implementation of P5 (Strengthening the Profile of Pancasila Student Project) at MI Ikhlasiyah Palembang. This study is a field research with a qualitative descriptive approach. Data collection methods include interviews, observations, and documentation. Data analysis techniques involve data collection, data presentation, verification, and conclusion drawing. Based on the results and discussions, the implementation of P5 at MI Ikhlasiyah Palembang has been carried out well through various learning activities with the aim of strengthening the Pancasila student profile and increasing knowledge and application of Pancasila ideals for students. In its implementation, students will participate in social activities related to the Pancasila ideals and receive comprehensive understanding of the Pancasila principles. This implementation can also improve the attitudes and behaviors of children.